STUDI TENTANG VARIASI PELAMINAN DI SENTRA PELAMINAN KECAMATAN LUBUK BEGALUNG KOTA PADANG - Ridya Febriani; Jupriani .; Minarsih . (Serupa The Journal of Art Education, 2012)
Abstract Minangkabau wedding rich in visual variations. As the center aisle, District Lubuk Begalung deemed to know and be able to answer the research objectives, describing 1) Variations in raw material 2) color variations. 3) Variations in the arrangement of elements weddings. Descriptive qualitative research method. Sources of data in the form of oral testimony from informants and literature library. The procedure of collecting data through observation, interviews and documentary study. Data were analyzed by performing data reduction, display and conclusion. Checking the validity of the findings made ​​by the technique of triangulation. Based on the results of data found that: 1) the basic ingredients of the aisle velvet, sateen fabric, lame, spoonhard 2) wedding colored red, yellow, green, blue, turning to silver, back to the many colors, 3) structuring element of the aisle, ceiling, rectangular, square bagonjong, Osborne-Osborne half circles, triangles, tongues and cancang, payuang one level and two-level, stems wrapped in cloth and spoonhard katorok. Banta gadang mounted single, double parallel and there are no double parallel, wedding chair shaped sofa, wearing the crown, circular and terraced. Box envelope single-legged and more. Based on the findings, it was concluded: 1) the basic ingredients aisle no velvet, satin, lame fabric and spoonhard.2) wedding colors like red, yellow, green, blue, and silver. 3) aisle display varies from langik-langik aisle, Osborne-Osborne, payuang, banta gadang, chairs, and a box envelope. Kata Kunci : pelaminan, warna, bahan dasar